Body mass changes and voluntary fluid intakes of elite level water polo players and swimmers - Cox, G. R.; Broad, E. M.; Riley, M. D.; Burke, L. M. (Journal of Science and Medicine in Sport, 2002)
Calculated sweat rates (measured by body mass changes) and voluntary fluid intakes were monitored in elite level water polo players and swimmers during normal exercise sessions to determine fluid requirements to maintain fluid balance, and the degree of fluid replacement of these athletes. Data were collected from training and competition sessions for male water polo players (n = 23) and training sessions only for swimmers (n = 20 females; n = 21 males). The calculated average sweat rate and fluid intake rate during training sessions for male water polo players was 287 ml/h and 142 ml/h, respectively, with a rate of 786 ml/h and 380 ml/h during matches. During training sessions for male swimmers, the calculated average sweat rate and fluid intake rate per kilometre was 138 ml/km and 155 ml/km, respectively; and for female swimmers, 107 ml/km and 95 ml/km. There was a wide individual variation in fluid intake and sweat loss of both water polo players and swimmers. Dehydration experienced by athletes in this study was less than typically reported for "land-based" athletes. Errors inherent in the technique used in this study are acknowledged and may be significant in the calculation of reported sweat losses and levels of fluid balance in aquatic athletes.